THE NEXUS BETWEEN JKN QUALITY, EMPLOYEE PERFORMANCE, AND PATIENT SATISFACTION - Enggarwati, Rumi; Retno Endah Supeni; Toni Herlambang (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The National Health Insurance Program (JKN) is designed to improve the overall quality of public health while providing protection to individuals and families from the burden of high health care costs. The quality of National Health Insurance (JKN) services which are supported by human resource competencies such as speed, response to patient needs, and professionalism of medical personnel will improve employee performance and ultimately, this will have a positive impact on patient satisfaction. Method: This research was conducted at the Rambipuji Jember Community Health Center with 100 BPJS patients as respondents. The research instrument used a questionnaire. The data analysis technique uses SEM PLS. Results: The research results show that: (1) JKN quality has a positive and significant effect on employee performance, (2) JKN quality has a positive and significant effect on patient satisfaction, (3) Employee performance has a positive and significant impact on patient satisfaction,( 4) JKN quality has a positive and significant impact on patient satisfaction through employee performance. Novelty: This study aims to examine how the quality of JKN services at Puskesmas plays a role in influencing patient satisfaction. This is important for understanding the connection between national health policies and patient experiences at the primary care level. Additionally, the study investigates the role of Puskesmas staff performance as a mediator between JKN quality and patient satisfaction, which could provide new insights into the importance of human resources in improving patient experiences.